Abdominal lifting, effleurage, and deep back massages effective in reducing pain during active phase of first stage labor - Arantika Meidya Pratiwi; Isti Chana Zuliyati; Fatimatasari Fatimatasari (Alma Ata University Press, 2021)
Background : Although childbirth is a natural process, the time of childbirth makes women feel afraid, anxious and anxious, thus affecting the labor process which results in prolonged labor and neonatal asphyxia. Where prolonged labor is a complication of the cause of maternal death which is the fifth largest in Indonesia. Labor pain can affect the condition of the mother in the form of victims, fear, worry and can cause stress. Stress can cause the uterine contractions to weaken and lead to prolonged labor.Objective : This study was to analyze the effectiveness of abdominal lifting, effleurage and deep back massage techniques in reducing pain during active phase of first stage labor.Method : This study used one-group pretest-posttest design method with a total sample of 30 Participants mother in labor. There were 3 groups that were given treatment, each group was given one massage technique. Change in pain was measured by a numerical pain scale. Testing variables using the Wilcoxon test, comparison of each intervention test performed using Kruskall Wallis.Result : There is a significant difference in pain scores before and after giving abdominal lifting massage with a value of p = 0.005 (<0.05). There was a significant difference in pain scores before and after giving effleurage massage with a value of p = 0.011 (p <0.05). There is a significant difference in pain scores before and after giving Deep Back Masaage with a value of p = 0.004 (p <0.005). There was no significant difference in pain scores after treatment between the three groups with a value of p = 0.080 (p> 0.05).Conclusion : abdominal lifting, effleurage, and deep back massage are effective in reducing the pain during active phase of first stage labor. There was no significant difference between the three massage techniques in reducing labor pain.